Światowe tendencje w zakresie pomocy dla ofiar przestępstw - Gronowska, Bożena (Wydział Prawa i Administracji UAM, 1986)
Victimology in effect of its few dozens years of history reveals not only theoretical but also practical achievments. The present article is devoted to a study of world tendencies observed - in that second domain, i.e. in the sphere of offering materiali aid for crime victims both by a State and society. On the grounds of accesible world literature the authoress makes an attempt at classifying the present effects of practical directions in victimology (mainly in the USA, Canada., Australia and some Western European states). Presently one can speak of three basic aid programs for crime victims, i.e.: 1) the compensation program, 2) victim-witness assistance program, 2) victim restoration program. Apart from necessary data on detailed tasks- of the programs the authoress quotes also some additional information on the newest problems of the state compensation for crime victims, practical effect of the victim-witness assistance and the use of restitution and other actions directed at the ,re-adaptation of crime victims. At the conclusion, the world trends in that scope are presented, those which manifested themselves at the fore of the VIIth United Nations Congress on preventing crime and proceeding with the victims of crime. (Milan, 1985).
The World Tendencies i n Aid for Crime Victims